Shaping Prosocial Behavior in Kindergarten Children Through Bedtime Storytelling - Yuni Istikomah, Ela; Bawono, Yudho; Purwo Wibowo, Wasis (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: Prosocial behavior typically begins to emerge when a child is around two years old, an age that falls within the early childhood stage. Children of kindergarten age are also considered to be in early childhood. At this stage, children tend to exhibit prosocial behaviors primarily toward those closest to them, such as family members, teachers, and classmates. The development of prosocial behavior is crucial for early childhood, as it prepares children to become members of a community and helps them adapt and interact within a broader social environment in the future. Factors that support the emergence of prosocial behavior include a positive environment, effective communication, observable role models, good habits, and parental involvement. One way parents can contribute is by engaging in bedtime storytelling. Aims and scope of paper: This study aims to explore and understand prosocial behavior in kindergarten-aged children who are regularly told bedtime stories. Methods: This research employs a qualitative method with a case study approach. The sampling technique used is purposive sampling, involving three participants aged 4–6 years who are enrolled as students at TK Anak Sholeh, Bangkalan. Data were collected through interviews and analyzed using Stake’s data analysis model. The validity of the data was ensured through source triangulation. Results: The study found that all three participants demonstrated prosocial behavior across several key aspects. These behaviors include the ability to express empathy, collaborate, share tasks with peers, help others, donate willingly, and acknowledge their mistakes. In summary, the results indicate that the three kindergarten-aged participants exhibited prosocial behaviors such as sharing, cooperation, helping, donating, and honesty. Contribution: This study concludes that bedtime storytelling can effectively foster prosocial behavior in kindergarten-aged children. Therefore, it is recommended that parents pay closer attention to their children's prosocial development and support it by establishing a consistent bedtime storytelling routine.